The Effect of Leg Muscle Training on Shooting Ability in Players of the Bunga Kenanga Futsal Club in Bengkulu City - Paulinsia, Liza; Martiani, Martiani; Banat, Azizatul (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of leg muscle training on shooting in Bunga Kenanga Futsal Club players in Bengkulu City. This type of research is an experimental study with a sample of 18 players. Based on the results of the research that has been done, the results of the initial test (Pre-Test) and the final test (Post-Test) that have been carried out, it can be concluded that leg muscle training has a significant effect on shooting in Bunga Kenanga futsal club players which shows that the t count value (4.07) > t table value (1.734). The average value of 33.33 in the initial test and after being given leg muscle strength training treatment there was an increase in the average value of 40.28. In addition to the increase in the average value of the final test (Post-Test), it is also seen in the analysis of data description, where in the initial test the sample obtained a score of 10 people (56%) with a poor classification, as many as 8 people (44%) with a moderate classification and no players with a good and very good classification and very poor while in the post-test obtained as many as 3 people (17%) with a poor classification, as many as 11 people (61%) with a moderate classification, as many as 4 people (22%) with a good classification and no players with a very poor and very good classification.